A case of preeclampsia developing massive ascites after delivery. Issue 5 (15th May 2022) - Higami, Shota; Kondo, Emi; Shibata, Eiji; Fujimoto, Shigeki; Hagimoto, Marina; Urakawa, Ruka; Matsumiya, Tamaki; Uchimura, Takayuki; Sakuragi, Toshihide; Amimoto, Shoko; Kuwazuru, Tomoichiro; Mori, Hiroshi; et al.
Abstract: We experienced a case of preeclampsia in which massive ascites became apparent in the postpartum period. The patient had isolated proteinuria without hypertension before delivery. The infant had fatal growth restriction and neonatal distress. Massive ascites and isolated proteinuria are important symptoms for predicting the aggravation of PE. Abstract : If an abdominal extension is observed as in this case, it is necessary to consider ascites retention in the management of aggravated PE.